Manajemen Pemupukan N-P-K dengan Pupuk Hayati untuk Mempertahankan Kandungan N dan P Tanah serta Hasil Kedelai - Emma Trinurani Sofyan; Stefina Liana Sari (Jurusan Agroteknologi, 2017)
One effort to increase the productivity of soybeans in Inceptisols Jatinangor is through utilize inoculant of soil microorganisms such as nitrogen-fixing bacteria and phosphate-solubilizing bacteria in the form of specific biofertilizer (SB) for soybean plant without leaving inorganic fertilizer as a source of available nutrients to plants. This research aimed to determine fertilization management of N-P-K and specific biofertilizer in retaining N and P availability and yield of soybean. The Research was conducted from April to July 2016, arranged in Simple Randomized Block Design (RBD) and consisted of 10 treatments. The combination of biofertilizer and N-P-K were as follows; A = control (without fertilizer), B = Standard N-P-K, C = 0 N-P-K + 1 SB , D = 1/4 N-P-K + 1 SB, E = 1/2 N-P-K + 1 SB, F = 3/4 N-P-K + 1 SB, G = 1 N-P-K + 1 SB, H = 3/4 + 1/4 SB, I = 3/4 N-P-K + 1/2 SB dan J = 3/4 N-P-K + 3/4 SB. The results showed a dose of N-P-K and biofertilizer was recommended in the treatment E (250 kg ha-1 SB) and 1/2 N-P-K (37.5-50-50 kg ha-1). The dose was able to increase nitrogen and phosphor content in soil and plant, also on yield of soybean up to 0.4 t ha-1 or 32% of a standard N-P-K.